Konstruksi Tipologi Pendusta Agama dalam QS. Al-Ma’un: Analisis Tafsir Tahlili - Andi Dian Wulandari; Halimah Basri; Ahmad Mujahid (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
The phenomenon of denying religion in surah Al-Mā‘ūn is generally understood as a form of deviant socio-religious behavior; however, it has not been systematically examined from an exegetical perspective. Therefore, this research aims to analyze the meaning of surah Al-Mā‘ūn/107:1–7 using a tahlili interpretation approach and to formulate a typology of religious hypocrites based on the indicators present in the verse. The study focuses on interpreting surah Al-Mā‘ūn/107:1–7 through an analytical lens to identify indicators of religious hypocrisy, which will then serve as the foundation for developing a typology. This research is conducted as library research using qualitative methods. Data analysis involved verse inventory, vocabulary analysis, and synthesis of interpretations from various commentators. The findings indicate that the concept of religious hypocrite in surah Al-Mā‘ūn is not solely tied to belief but also illustrates a disconnect between ritual piety and social responsibility. Consequently, three primary typologies of religious hypocrites were formulated: social, ritual, and moral typologies. The novelty of this research lies in constructing a typology of religious deceivers that is systematically organized through an analytical interpretation approach based on behavioral indicators found in surah Al-Mā‘ūn. This study contributes to the advancement of Quranic exegesis and is pertinent for enhancing moral education and socio-religious awareness.